Digitalization of Ar-Ramz for The Disabled in Welcoming The Era of Society 5.0: Digitalisasi Ar-Ramz untuk Kaum Difabel dalam Menyongsong Era Masyarakat 5.0 - Ekaputra, Muhammad Iqbal Wi’an; Anwar, Najih (Universitas Muhammadiyah Sidoarjo, 2025)
The era of society 5.0 demands the integration of technology in all aspects of life, including for people with disabilities. Unfortunately, accessibility of technology for people with disabilities is still low due to limited infrastructure, digital literacy, and the lack of technology that is friendly to people with disabilities. This article offers the concept of digitalization of sign language based on theology from the terminology of ar-ramz in the Qur'an as a solution for digital inclusion. The use of Augmented Reality (AR) technology and audiobooks is proposed to optimize the sensory potential of the blind and deaf. AR maximizes visuals for the deaf, while audiobooks optimize hearing for the blind. This concept is expected to increase the productivity and independence of people with disabilities and realize an inclusive digital culture. With the support of socialization, training, and cross-sector collaboration, inclusive digitalization can become a massive movement towards a just and disabled-friendly society 5.0. Highlights: Theological Basis: Utilizes ar-ramz from the Qur'an to frame sign language digitalization. Tech Optimization: AR aids the deaf; audiobooks support the blind for better engagement. Inclusive Push: Calls for training and collaboration to foster a just, accessible digital society. Keywords: Disabled, Ar-Ramz, Education